Practical CakePHP Projects - Chan, Kai (Apress, 2012)
First off, thank you for picking up this book. Whether you are standing in a bookshop or reading this at home, we assume you probably have a strong interest in developing web sites. In the past few years, the number of web site frameworks has increased dramatically. This is especially true for PHP-based frameworks. Many people have chosen to adopt CakePHP (Cake, for short) for various reasons, such as these